PENGARUH HARGA DAN PROMOSI TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN PERUMAHAN DI PT. RESSAN GEMOLONG - Kusumawati, Mega; Danarwati, Yanti Sri (Universitas Of Surakarta, 2020)
This study aims to analyze the effect of prices and promotions on housing purchase decision making at PT. Ressan Land Gemolong. The population in this study are all consumers who have come and made purchases at PT. Ressan Land Gemolong. The sample in this study consisted of 70 respondents using purposive sampling techniques. Data collection is done by using a survey through a questionnaire filled out by customers. Then, the data obtained were analyzed using multiple regression analysis. This analysis includes validity test, reliability test, classic assumption test, multiple linear regression analysis, hypothesis testing through t test and F test, and analysis of the coefficient of determination (R2). Based on the results of the study, the regression equation obtained the results Y = 19.113 + 0.462 X1 + 0.505 X2 + e. Based on the analysis of static data, the indicators in this study are valid and the variables are reliable. In testing classic assumptions, multicollinearity regression models, heteroscedasticity do not occur, and have a normal distribution. Individually, the variable that has a greater influence is the price with a regression coefficient of 0.505 and followed by a promotion variable with a regression coefficient of 0.462. Hypothesis calculation using t test shows that the price and promotion variables studied are proven to be significant. Then through the F test, it is clear that the independent variable is feasible to test the dependent variable of the purchase. The adjusted R square figure shows that 22.4% of purchasing decisions can be explained by promotion and price variables. While the rest is explained by other factors outside the research model.